Kualitas Produk, Citra Merek, dan Word Of Mouth terhadap Keputusan Pembelian - Ahmad Shafrizal; Hery Pudjoprastyono (IPM2KPE, 2022)
This study aims to determine the effect of product quality, brand image, and word of mouth on Xiaomi smartphone purchasing decisions. This research method is quantitative. The population in this study is Surabaya residents who use Xiaomi smartphones whose exact population size is not known. The sampling technique uses purposive sampling and uses non-probability sampling methods. Respondents obtained 70 residents. Data collection was carried out through a Google form questionnaire to respondents with an ordinal scale via a Likert scale from a score range of 1 to 5. The data was processed using the Partial Least Square (PLS) data analysis technique. The results showed that product quality, brand image, and word of mouth had a positive and significant effect on Xiaomi smartphone purchasing decisions in Surabaya. In conclusion, product quality, brand image, and word of mouth have a significant influence on purchasing decisions. Keywords: Brand Image, Purchase Decision, Product Quality, Word of mouth